Undergraduate Disabled Students as Knowledge Producers Including Researchers: Perspectives of Disabled Students - Aspen Lillywhite; Gregor Wolbring (MDPI AG, 2022)
Knowledge influences policy development and policies impact disabled people. Scientific and technological advancements, including neuro-advancements and their governance, have social implications for disabled people. However, knowledge is missing on this topic. Although efforts are underway to increase the number of disabled academics, the numbers remain low. Engaging undergraduate disabled students in knowledge production, especially research, could decrease the knowledge deficit and increase the pool of disabled students considering an academic career. We performed 10 semi-structured interviews of disabled students to understand the reality of undergraduate disabled students as knowledge producers, including researchers. Using a directed thematic content analysis, we found that participants felt that undergraduate disabled students were insufficiently exposed to and supported in the identity of being knowledge producers including researchers. Participants identified ethical, legal, and social implications of science and technology and argued that undergraduate disabled students and disabled people have a role to play in the discussions of these. Exposing disabled students at the undergraduate and high school level to knowledge production including researcher identity could increase the numbers of undergraduate disabled researchers, disabled academics, and disabled students doing research in the community after graduation and decrease the knowledge gaps around the social situation of disabled people.